Second-order judgment problems : the impacts of perceived social distance on judgment making - Park, Mina (2021)
Judgment making about targets in information-abundant environments involve another level of judgement processes to sort out relevant and trustworthy information about the targets of judgment. We call this second-order judgment problems. The present study formulated second-order judgement problems into a theoretical model that focuses on the impacts of perceived social distance between a target and the informant who provides the information about the target on judgement formation processes. A set of hypotheses were developed and tested through a web-administrated experiment, in which participants were asked to make judgments in a hypothetical criminal incidence based on the information provided by multiple sources. The results suggested that perceived distance between targets and information sources had positive effects on trustworthiness of information as well as final judgment. However, the effects were found nonlinear, suggesting the possibility of compounded effects. This paper concluded with discussion of the implications of the current findings.